The Health Promotion Model in HIV Care - Yeow Chye Ng (Aquichan, 2016)
Effective medical treatment with uninterrupted engagement in care is critical to improving the survival and the quality of life of patients infected with the human immunodeficiency virus (HIV). Objectives: Multiple behavioral interventions have been conducted to promote adherence behaviors. However, adherence to HIV medications and medical appointments is still an issue of global concern. Method: The Health Promotion Model (HPM) is a nursing adaption of the health belief model. The HPM focuses on individual characteristics and expe- riences, as well as behavior specific cognitions and outcomes. Integrating the HPM in addressing adherence behaviors could be one of the building blocks of success in changing health behavior. Results: A search of the literature turned up no studies that applied the HPM in adherence behavior studies conducted among HIV-infected populations. Conclusion: This paper presents the reader with the availability of current adherence-behavior interventions and strategies that align with the HPM model components. It further proposes the need for medi- cal treatment team members to adopt the HPM in current clinical practice settings so as to effectively address adherence behavior issues.